Assessment impact of land use land cover changes the water yield - Nurul ellyanna , Kamaruddin (2015)
Quantity is the first attribute of a water service that many people consider. The main source of water is rainfall. Although an eco-system itself does not create the water, it does modify the amount of water moving through the landscape. The main of the study will be assessing the impact of land use and land cover changes to the water-yield. The specific of study will be as follow; to determine the satellite-based water-yield of study area, to determine the satellite-based land use land cover (LULC) changes, and to analysis the relationship between satellite-based water-yield and land use land cover (LULC) changes. ' Water-yield will be estimate with simple hydrology cycle relationship. Tropical Rainfall Measuring Mission Multi-satellite Precipitation Analysis (TMPA) satellite-based monthly rainfalls obtained from public domain were used as input. Meanwhile, actual evapotranspiration were estimate using satellite-based biophysical index (i.e. Normalized Difference Vegetation Indices (NDVI)) and will use as output. LULC changes also will be determined using satellite-based NDVI. The relationship between satellite-based water-yield and land use land cover (LULC) changes will be statistically analyzed. The result shows, relationship strength between satellite-based water-yield and land use land cover (LULC) changes.